Pengaruh Profesionalisme, Komitmen dan Kinerja Pegawai Terhadap Kepuasan Masyarakat pada Kementerian Agraria dan Tata Ruang (ATR/BPN) Kota Padang - Datamora, Sandro; Lanin, Dasman (JESS (Journal of Education on Social Science); Vol 6 No 02 (2022): Public Servant vs Public Service in Digital Era, 2023)
This research was motivated by the lack of optimal community satisfaction in the Ministry of Agrarian and Spatial Planning (ATR / BPN) of Padang City . This study aims to analyze: 1) the effect of professionalism on community satisfaction; 2) the effect of commitment on the quality of community satisfaction; 3) the effect of employee performance on community satisfaction; 4) the simultaneous influence of professionalism, commitment and employee performance on community satisfaction in the Ministry of Agrarian and Spatial Planning (ATR / BPN) of Padang City. In this study, the population is the entire Padang City Community who have received services at the Office of the Ministry of Agrarian and City Spatial Planning (ATR / BPN) of Padang City. From the calculation of the Slovin formula above, the number of samples obtained from the calculation results above is 131 samples. Data collection is carried out by survey method with questionnaire. The data analysis techniques used in this study are descriptive and quantitative analysis. The data collected are primary and secondary data that can be classified as independent variables and dependent variables. Hypothesis testing in this study used multiple linear regression tests. The results showed that (1) Professionalism has a positive and significant effect on community satisfaction in the Ministry of Agrarian and Spatial Planning (ATR / BPN) of Padang City. (2) Commitment has a positive and significant effect on community satisfaction in the Ministry of Agrarian and Spatial Planning (ATR / BPN) of Padang City. (3) Employee performance has a positive and significant effect on community satisfaction in the Ministry of Agrarian and Spatial Planning (ATR / BPN) of Padang City. (4) Professionalism, commitment and employee performance have a positive and significant effect on community satisfaction in the Ministry of Agrarian and Spatial Planning (ATR / BPN) of Padang City. Keywords : Professionalism, Commitment, Employee Performance, Community Satisfaction